Sosialisasi Mitigasi Bencana Hidrometeorologi Pada Masyarakat Desa Rodaya Kabupatan Bengkayang Kalimantan Barat - Muliadi Muliadi; Warsidah Warsidah (Indonesian Journal Publisher, 2024)
The flood disaster is one of the hydrometeological disasters that affects areas throughout the country, especially when the rainy season arrives. The risk of flooding can occur when there is high rainfall or heavy rain, or when a river overflows from a higher area so that it will flow to a lower area until it is submerged. The area of ​​Dusun Baya, Rodaya Village, Bengkayang Regency is one of the areas submerged by a 2-meter flood in March 2023. This community service activity (PKM) with the implementation team from Tanjungpura University aims to socialize a series of activities to anticipate disasters by organizing them in an appropriate and efficient manner. efficient for the people of Rodaya village, Ledo sub-district, Bengkayang Regency, West Kalimantan. This activity was attended by 25 participants from Rodaya village, namely from Baya hamlet as many as 15 people and the remaining 10 people from Segiro hamlet and Sedane hamlet. The activity was carried out using lecture and discussion methods by the presenters who were the team implementing the activity. Monitoring that took place during lectures and discussions showed very high community enthusiasm. Based on the results of the activity evaluation through questionnaires at the beginning and end of the activity, it shows that there has been an increase in the basic knowledge of the Rodaya village regarding flood disasters and ways to deal with them from average 40-60% to 80-100%.